Baseline low-density lipoprotein cholesterol to predict the extent of cardiovascular benefit from lipid-lowering therapies: a review. Issue 1 (21st September 2018) - Navarese, Eliano P; Andreotti, Felicita; Raggi, Paolo; Kołodziejczak, Michalina; Buffon, Antonino; Bliden, Kevin; Tantry, Udaya; Kubica, Jacek; Sardella, Gennaro; Lauten, Alexander; Agewall, Stefan; Gurbel, Paul A; et al.
Abstract: Lipid-lowering therapies have been shown to improve cardiovascular outcome in a wide range of patients. The current guidelines recommend a graded approach to reduction in low-density lipoprotein cholesterol (LDL-C) proportional to the patient's risk, with the goal of achieving either a certain magnitude of reduction or a specific threshold of final LDL-C. Recent findings from a meta-analysis of numerous randomized trials suggest that more attention should be given to the baseline LDL-C of an individual patient. In this review, we discuss how the baseline LDL-C level may provide a means to better understand the results of recent cardiovascular outcome trials and the expected benefits of lipid-lowering therapies. The exact quantification of the clinical benefit associate with an intensified lipid-lowering therapy depends on the baseline LDL-C. Mortality is reduced in a log-linear fashion only when LDL-C > 100 mg/dL.